Combining Cytotoxicity Assessment and Xenopus laevis Phenotypic Abnormality Assay as a Predictor of Nanomaterial Safety. Issue 1 (4th August 2017) - Al‐Yousuf, Karamallah; Webster, Carl A.; Wheeler, Grant N.; Bombelli, Francesca Baldelli; Sherwood, Victoria
Abstract: The African clawed frog, Xenopus laevis, has been used as an efficient pre‐clinical screening tool to predict drug safety during the early stages of the drug discovery process. X. laevis is a relatively inexpensive model that can be used in whole organism high‐throughput assays whilst maintaining a high degree of homology to the higher vertebrate models often used in scientific research. Despite an ever‐increasing volume of biomedical nanoparticles (NPs) in development, their unique physico‐chemical properties challenge the use of standard toxicology assays. Here, we present a protocol that directly compares the sensitivity of X. laevis development as a tool to assess potential NP toxicity by observation of embryo phenotypic abnormalities/lethality after NP exposure, to in vitro cytotoxicity obtained using mammalian cell lines. In combination with conventional cytotoxicity assays, the X. laevis phenotypic assay provides accurate data to efficiently assess the safety of novel biomedical NPs. © 2017 by John Wiley & Sons, Inc.